Application of a reverse dot blot DNA–DNA hydridization method to quantify host‐feeding tendencies of two sibling species in the Anopheles gambiae complex. Issue 4 (5th March 2013) - FRITZ, M. L.; MILLER, J. R.; BAYOH, M. N.; VULULE, J. M.; LANDGRAF, J. R.; WALKER, E. D.
Abstract : A DNA–DNA hybridization method, reverse dot blot analysis (RDBA), was used to identify Anopheles gambiae s.s . and Anopheles arabiensis (Diptera: Culicidae) hosts. Of 299 blood‐fed and semi‐gravid An. gambiae s.l . collected from Kisian, Kenya, 244 individuals were identifiable to species; of these, 69.5% were An. arabiensis and 29.5% were An. gambiae s.s . Host identifications with RDBA were comparable with those of conventional polymerase chain reaction (PCR) followed by direct sequencing of amplicons of the vertebrate mitochondrial cytochrome b gene. Of the 174 amplicon‐producing samples used to compare these two methods, 147 were identifiable by direct sequencing and 139 of these were identifiable by RDBA. Anopheles arabiensis bloodmeals were mostly (94.6%) bovine in origin, whereas An. gambiae s.s . fed upon humans more than 91.8% of the time. Tests by RDBA detected that two of 112 An. arabiensis contained blood from more than one host species, whereas PCR and direct sequencing did not. Recent use of insecticide‐treated bednets in Kisian is likely to have caused the shift in the dominant vector species from An. gambiae s.s . to An. arabiensis . Reverse dot blot analysis provides an opportunity to study changes in host‐feeding by members of the An. gambiae complex in response to the broadening distribution of vector control measures targeting host‐selection behaviours.